2019
DOI: 10.1111/flan.12427
|View full text |Cite
|
Sign up to set email alerts
|

A survey of world language cooperating teachers: Implications for teacher development

Abstract: In an era of long‐standing world language teacher shortages, the preservice mentoring process has become even more critical. Using data from a national survey, this study provides a profile of PreK–12 world language cooperating teachers (CTs) and shares their beliefs about and perspectives on the teacher candidates with whom they work, their interactions with postsecondary stakeholders, their reasons for serving as CTs, and the challenges that inhibit the smooth and meaningful induction of new colleagues into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
(64 reference statements)
1
7
0
Order By: Relevance
“…To further inspire and motivate this new generation of learners, researchers in higher education teaching and learning recommend that educators show their passion for their disciplines (Bain, 2004; Cavanagh, 2016). This recommendation aligns with a recent nationwide study conducted by Moser et al (2019) where they discovered that cooperating WL teachers (82%, n = 233) decided to become mentors of teacher candidates because they desired to set the standards high for the next generation of WL teachers, charging them with “the responsibility to improve WL education” (p. 880).…”
Section: Literature Reviewsupporting
confidence: 75%
See 2 more Smart Citations
“…To further inspire and motivate this new generation of learners, researchers in higher education teaching and learning recommend that educators show their passion for their disciplines (Bain, 2004; Cavanagh, 2016). This recommendation aligns with a recent nationwide study conducted by Moser et al (2019) where they discovered that cooperating WL teachers (82%, n = 233) decided to become mentors of teacher candidates because they desired to set the standards high for the next generation of WL teachers, charging them with “the responsibility to improve WL education” (p. 880).…”
Section: Literature Reviewsupporting
confidence: 75%
“…Kissau et al (2019) also found that WL teacher education candidates, regardless of their age, expressed a desire to inspire and influence their future students positively. These participants seemed to accept the mission of WL in-service teachers mentioned by Moser et al (2019) to improve and even transform WL education.…”
Section: Experiences With Professors and Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…Giboney Wall (2016) refers to helping preservice teachers "make the invisible visible" through critical reflection. Positive models of standards-based teaching (García et al, 2019), observations of successful educators (Moser et al, 2019), and deconstruction of high-leverage teaching practices for novice teachers (Zhai, 2019) answer that call by highlighting particular teaching practices worthy of emulation. The premise of the present study is that certain elements of nonexemplary teaching may also be invisible to preservice teachers.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, that exposure comes through live classroom experience with mentor teachers who "model 21st century standards-based instruction" (García et al, 2019;p. 174) and "have demonstrated success as educators" (Moser et al, 2019;p. 884).…”
Section: The Methodology Course and Observationmentioning
confidence: 99%